A quantitative evaluation of the extent of fluralaner uptake by ticks (Ixodes ricinus, Ixodes scapularis) in fluralaner (BravectoTM) treated vs. untreated dogs using the parameters tick weight and coxal index - Heike Williams; Janina Demeler; Janina Taenzler; Rainer K.A. Roepke; Eva Zschiesche; Anja R. Heckeroth (Parasites & Vectors, 2015)
Abstract Background Fluralaner is a new antiparasitic drug that was recently introduced as BravectoTM chewable tablets for the treatment of tick and flea infestations in dogs. Most marketed tick products exert their effect via topical application and contact exposure to the parasite. In contrast, BravectoTM delivers its acaricidal activity through systemic exposure. Tick exposure to fluralaner occurs after attachment to orally treated dogs, which induces a tick-killing effect within 12 h. The fast onset of killing lasts over the entire treatment interval (12 weeks) and suggests that only marginal uptake by ticks is required to induce efficacy. Three laboratory studies were conducted to quantify the extent of uptake by comparison of ticks’ weight and coxal index obtained from BravectoTM-treated and negative-control dogs. Methods Three studies were conducted using experimental tick infestation with either Ixodes ricinus or Ixodes scapularis after oral administration of fluralaner to dogs. All studies included a treated (BravectoTM chewable tablets, MSD Animal Health) and a negative control group. Each study had a similar design for assessing vitality and weighing of ticks collected from dogs of both groups. Additionally, in one study the coxal index (I. ricinus) was calculated as a ratio of tick’s ventral coxal gap and dorsal width of scutum. Tick weight data and coxal indices from BravectoTM-treated and negative-control groups were compared via statistical analysis. Results Ticks collected from BravectoTM-treated dogs weighed significantly less (p ≤ 0.0108) than ticks collected from negative-control dogs, and their coxal index was also significantly lower (p < 0.0001). The difference in tick weights was demonstrated irrespective of the tick species investigated (I. ricinus, I. scapularis). At some assessments the mean tick weights of BravectoTM-treated dogs were significantly lower than those of unfed pre-infestation (baseline) ticks. The demonstrated tick-killing efficacy was in the range of 94.6 – 100 %. Conclusions Tick weights and coxal indices confirm that a minimal uptake results in a sufficient exposure of ticks to fluralaner (BravectoTM) and consequently in a potent acaricidal effect.